Ethical and legal concepts: responsibility, accountability and liability. (2nd September 2021) - Ellis, Peter; Ellis, Hannah
Abstract : Peter and Hannah Ellis outlines the differences between responsibility, accountability and liability, as well as how each definition relates to the kidney care professional